EU-Mercosur Agreement: Developments and Prospects for Bulgarian-Brazilian Economic and Trade Relations (UNWE Yearbook, 2021)
As the signing of the Free Trade Agreement between the European Union and the Southern Common Market is a fact, the paper aims at revealing the impacts and the prospects of it on the Bulgarian-Brazilian economic and trade relations. After presenting the EU-Mercosur trade context briefly, it discusses the dynamics of the bilateral trade flows both between the European Union and Mercosur and, Bulgaria and Brazil and, emphasises on the novelty of the features and opportunities. The prospects for future economic developments are stated.